1992
DOI: 10.1136/jnnp.55.4.255
|View full text |Cite
|
Sign up to set email alerts
|

Serial MRI and neurobehavioural findings after mild to moderate closed head injury.

Abstract: Fifty patients who sustained mild to moderate closed head injury (CHI) underwent a CT scan, MRI, and neurobehavioural testing. At baseline 40 patients had intracranial hyperintensities detected by MRI which predominated in the frontal and temporal regions, whereas 10 patients had lesions detected by CT. Neurobehavioural data obtained during the first admission to hospital disclosed no distinctive pattern in subgroups of patients characterised by lesions confined to the frontal, temporal, or frontotemporal regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
101
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(110 citation statements)
references
References 20 publications
8
101
1
Order By: Relevance
“…The poorer verbal memory of the mild TBI group also confirms the findings of previous studies undertaken with mild TBI patients (e.g., Dikmen et al, 1986;Stuss et al, 1985). Finally, the failure to find deficits in the verbal fluency skills of the mild TBI group is consistent with the findings of Leininger et al (1990) but not with those of Fos et al (1995), Levin et al (1991), and Mathias and Coats (1999). Non-verbal fluency, on the other hand, was clearly compromised in the mild TBI group; a finding supported by Levin et al (1987Levin et al ( , 1991 in the acute stages after a mild TBI (around the time of the injury) but not in the more chronic phases (i.e., 1-3 months post injury).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The poorer verbal memory of the mild TBI group also confirms the findings of previous studies undertaken with mild TBI patients (e.g., Dikmen et al, 1986;Stuss et al, 1985). Finally, the failure to find deficits in the verbal fluency skills of the mild TBI group is consistent with the findings of Leininger et al (1990) but not with those of Fos et al (1995), Levin et al (1991), and Mathias and Coats (1999). Non-verbal fluency, on the other hand, was clearly compromised in the mild TBI group; a finding supported by Levin et al (1987Levin et al ( , 1991 in the acute stages after a mild TBI (around the time of the injury) but not in the more chronic phases (i.e., 1-3 months post injury).…”
Section: Discussionsupporting
confidence: 82%
“…Finally, the failure to find deficits in the verbal fluency skills of the mild TBI group is consistent with the findings of Leininger et al (1990) but not with those of Fos et al (1995), Levin et al (1991), and Mathias and Coats (1999). Non-verbal fluency, on the other hand, was clearly compromised in the mild TBI group; a finding supported by Levin et al (1987Levin et al ( , 1991 in the acute stages after a mild TBI (around the time of the injury) but not in the more chronic phases (i.e., 1-3 months post injury). Importantly, the effects observed here accord very well with those reported by Zakzanis et al (1999) who noted, in their meta-analysis of mild TBI research, that the domains with the greatest observed deficits are cognitive flexibility (assessed here by the RFFT, COWA), followed by delayed recall (RAVLT short and long delayed recall), memory acquisition (RAVLT Trials 1-5), attention and concentration (TEA subtests) and verbal ability (not assessed).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Following TBI, patients have significantly reduced quality of life (QoL) and cognitive indices (15,16). Symptoms of fatigue are further exacerbated in the presence of growth hormone (GH) deficiency (GHD) compared with patients with normal GH reserve (17).…”
Section: Introductionmentioning
confidence: 99%